Climate pattern, snow- and timberlines in the Altai Mountains, Central Asia - Klinge, Michael; Böhner, Jürgen; Lehmkuhl, Frank (ERDKUNDE, 2003)
In the sparse populated areas of Central and High Asia, where climate measurements are rare and spatial climate data has to be interpolated from few meteorological stations, the geo-ecological environments provide detailed information about climate patterns. With the help of a high-resolution spatial climate-analysing scheme the potential area of geo-ecological zones, like glaciations and forests, can be outlined. Comparing these results with empirical collected geo-information from topographic maps, air photos, fieldwork and literature creates an instrument to evaluate the model and to estimate the climate patterns, which control the variation of geomorphologic features and vegetation associations. In a further step the past and future ecological environments can be delineated by these climate parameters. The investigation area in the Altai and Khangay mountains borders the Siberian taiga in the north to the desert and steppe regions of Central Asia in the south. A typical character of the boundary zone between the woodland and steppes in this region is, that the forests, exclusively constituted of larch trees (Larix sibirica), are restricted to the northern side of the slopes. The minor solar radiation input on the north facing slopes arouses less transpiration than on the southern slopes, where mountain steppe occurs. Low annual air temperatures effect the development of discontinuous permafrost. This leads to better soil water supply and larch trees are able to grow at sites with less precipitation than 200 mm/a. While low summer temperatures mainly control the upper timberline, the lower closed forest boundary is limited by the amount of precipitation. The number of tree species and also the vertical extension of forests in the Altai and Khangay mountains increase with more precipitation. The upper timberline in the Altai rises steeply from 1,000 m to 2,000 m at the western border. Above the central and southeastern Altai and in the Khangay Mountains it remains in a relatively constant elevation between 2,400 m and 2,600 m. At several places it reaches more than 2,800 m. In the northern Altai, the Sayan and in the eastern Khan Khukhiyn Mountains the upper timberline remains below 2,200 m. The lower forest boundary steadily rises from 800 m in the west and north to 2,200 m in the dry centre of the Altai. It steeply rises from 1,500 m in the southwest to 2,500 m in the northeast of the southern Altai. In the Khangay the lower forest boundary declines with the increasing precipitation from 2,250 m in the southwest to 1,250 m in the northeast. The climatic indications of the snowline coincide with those of the timberlines. In the Altai Mountains the altitude of the snowline is predominantly controlled by the decrease of precipitation to the southeast. The snowline rises from 2,600 m in the northwestern part to more than 3,800 m in the southeast and changes its latitudinal course into a longitudinal direction above the central Altai. The variation of the snowlines in regard to the slope aspects of one mountain system provides information for the local precipitation distribution and points to the main direction of wet air masses. Although most of the precipitation in the Altai is coming from western directions, in the southern Altai a huge quantity of precipitation is also coming from the southwest.